2013
DOI: 10.1089/ten.tea.2012.0163
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibitor Trichostatin A Promotes Proliferation and Odontoblast Differentiation of Human Dental Pulp Stem Cells

Abstract: Trichostatin A (TSA) is a potent histone deacetylase (HDAC) inhibitor with a broad spectrum of epigenetic activities known to regulate diverse cellular mechanisms, including differentiation of mesenchymal stem cells. In this study, we demonstrate that TSA promotes proliferation and odontoblast differentiation of human dental pulp stem cells (hDPSCs) in vitro and has the ability to enhance dentin formation and odontoblast differentiation in vivo during tooth development. We observed that TSA increased the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 42 publications
6
94
1
Order By: Relevance
“…showed that an HDAC inhibitor had the same effects on SCAPs as those reported by Jin et al on DPSCs 13) .…”
Section: In Conditioned Medium Lbh5and 589 Enhanced the Osteogenic Dsupporting
confidence: 73%
See 1 more Smart Citation
“…showed that an HDAC inhibitor had the same effects on SCAPs as those reported by Jin et al on DPSCs 13) .…”
Section: In Conditioned Medium Lbh5and 589 Enhanced the Osteogenic Dsupporting
confidence: 73%
“…As a global inhibitor of histone deacetylases, trichostatin A (TSA) has been shown to elevate the transcriptional activity of runx2 and, consequently, to initiate downstream gene transcription, eventually promoting osteoblast progenitor differentiation by inhibiting the activation of histone deacetylase 6. Jin et al reported that the histone deacetylase inhibitor TSA enhanced the efficiency of odontoblast differentiation in dental pulp stem cells (DPSCs) 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, VPA treatment led to an increased expression of osterix, osteopontin, BMP2, and Runx2 in human adipose tissue-derived stromal cells and bone marrow stromal cells [52]. Interestingly, TSA was shown to promote odontoblast differentiation of human dental pulp stem cells (hDPSCs) in vitro, and to enhance dentin formation and odontoblast differentiation in vivo during tooth development [53]. It is noteworthy that Hdacs inhibitors may achieve their promoting effects on osteogenic differentiation by inhibiting osteoclastogenesis [54,55,56].…”
Section: Resultsmentioning
confidence: 99%
“…Dental pulp cells cultured in vitro are able to form mineralization nodules at the site where cellular nodules exhibit multilayer growth and can aggregate under the effect of mineralization induction solution (Laiteerapong et al, 2012). Some studies have discovered that these mineralized nodules are primarily comprised of a dentin-like mineralized matrix, which has the characteristics of dentin (Jiang et al, 2012;Jin et al, 2013). Thus, at present, the formation of mineralized nodules is regarded as an important biological indicator of the detection of dentin generated in dental pulp cells (Du et al, 2013).…”
Section: Discussionmentioning
confidence: 99%